Mukjizat dan Iman dalam Injil Yohanes - Jhon Vetra Simatupang (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the theological significance of miracles in the Gospel of John within the framework of New Testament studies and their function as signs that lead people to knowledge of and faith in Jesus as the Messiah and the Son of God. Within a Christological framework, in the Gospel of John, miracles are presented selectively as theological signs designed to foster and affirm faith in Jesus Christ as the Messiah and the Son of God. This research adopts a qualitative methodology, utilizing a literature review and theological analysis of the miracle narratives in the Gospel of John. The analysis is conducted with particular attention to the Gospel's narrative structure and its declared purpose (John 20:30–31). The study's results demonstrate that the Gospel of John selectively presents certain miracles as signs imbued with deep theological meaning. These miracles not only manifest divine power but also disclose Jesus's identity and guide readers toward faith. The miracles in the Gospel of John should not be interpreted solely as supernatural events, but as instruments of divine revelation designed to cultivate and form faith. Faith constitutes the primary response to these signs, directing readers to confess that Jesus is the Christ, the Son of God, and that through faith in Him, eternal life is obtained.